ANALYSIS OF MAINTENANCE ACTIVITIES ON DRAG CHAIN MACHINES TO OPTIMIZE FAILURE TIME INTERVALS USING RELIABILITY CENTERED MAINTENANCE (RCM) APPROACH - Ariani, Farida; Juanda, Rizky Juanda (Talenta Publisher, 2023)
Drag Chain is a material moving machine whose working method is to deliver material using a continuous dragging method. Drag chain is the optimal choice for cement production, because the chain with conveyor leaves on the right and left side drags along the bottom of the trough to transport the material in a closed state. Under these circumstances the drag chain components will tend to wear out, as the material interacts directly with the chain and can cause problems. This research will explain the maintenance process using the Reliability Centered Maintenance (RCM) approach is a maintenance system which is associated with statistics to find the value of the reliability of a component so that we can prevent failure by a combination of various actions.